Skip beat!. Vol. 45 - Nakamura, Yoshiki; Kimura, Tomo (Shojo beat manga., 2021)
"Kyoko Mogami followed her true love Sho to Tokyo to support him while he made it big as an idol. But he's casting her out now that he's famous! Kyoko won't suffer in silence- she's going to get her sweet revenge by beating Sho in show biz! The news that Ren is dating a hot older woman is all over town, and Kyoko is doing her best to ignore it. But how can she pretend it isn't happening when Ren insists on talking to her about it?!"--